Traumatic Retinal Detachment - Williams, T.D. (Canadian Journal of Optometry, 2021)
At age 19, while playing tennis, the patient was struck in the right temple by a tennis ball. She contacted several eye care practitioners during the month following the accident, but no retinal problems were detected at any of these visits. Her first visit was sought primarily because of the recent eye injury: she had no symptoms at that time. A week later, the patient noted some flashing lights and arranged another consultation. No significant retinal problems were found at that time.